2013
DOI: 10.5463/dcid.v24i2.206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multisensory Training on Balance and Gait in Persons with Type 2 Diabetes: A Randomised Controlled Trial

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The inclusion criteria were as follows: 1) type II diabetes with a minimum duration of 5 years (11), 2) Fasting Blood Sugar (FBS( ≥7 mmol/l or 126 mg/dl (19),3) Glycated hemoglobin (HbA1c) between 7% and 9% (26), 4) Body Mass Index (BMI) between 25 and 29/9 kg/m 2 (27), 5) neuropathy diagnosed by a score higher than 2 out of the first part and higher than 1 out of the second part in the Michigan Neuropathy Screening Instrument (MNSI) (25) and score between 10-18 in the Valk questionnaire (28),6) ability to ambulate at least 10 meters without an assistive device (29), 7) strength of ankle dorsal/plantar flexors, invertors/evertors ≥ 3 by manual muscle testing (29), 8) at least 20/40 score in snellen dominant eye test chart (26),9) lack of foot and ankle ulcers at the time of the study (21), 10) lack of lower extremity sever pain at the time of the study (21), and 11) lack of regular physical training and physiotherapy intervention in the last three months (30). On the other hand, the exclusion criteria entailed: 1) lower extremity fractures and dislocation, 2) surgery or lower extremity amputation, 3) foot ulcers at study time, 4) cardiac autonomic neuropathy, 5) non-diabetic neuropathy, 6) vestibular system disorders, 7) internal ear infections, and 8) other balance disorders (30). Since condition 2 was assessed in the head hyperextension position, the vertebral artery involvement test was performed for all participants, and they were excluded if the results were positive.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were as follows: 1) type II diabetes with a minimum duration of 5 years (11), 2) Fasting Blood Sugar (FBS( ≥7 mmol/l or 126 mg/dl (19),3) Glycated hemoglobin (HbA1c) between 7% and 9% (26), 4) Body Mass Index (BMI) between 25 and 29/9 kg/m 2 (27), 5) neuropathy diagnosed by a score higher than 2 out of the first part and higher than 1 out of the second part in the Michigan Neuropathy Screening Instrument (MNSI) (25) and score between 10-18 in the Valk questionnaire (28),6) ability to ambulate at least 10 meters without an assistive device (29), 7) strength of ankle dorsal/plantar flexors, invertors/evertors ≥ 3 by manual muscle testing (29), 8) at least 20/40 score in snellen dominant eye test chart (26),9) lack of foot and ankle ulcers at the time of the study (21), 10) lack of lower extremity sever pain at the time of the study (21), and 11) lack of regular physical training and physiotherapy intervention in the last three months (30). On the other hand, the exclusion criteria entailed: 1) lower extremity fractures and dislocation, 2) surgery or lower extremity amputation, 3) foot ulcers at study time, 4) cardiac autonomic neuropathy, 5) non-diabetic neuropathy, 6) vestibular system disorders, 7) internal ear infections, and 8) other balance disorders (30). Since condition 2 was assessed in the head hyperextension position, the vertebral artery involvement test was performed for all participants, and they were excluded if the results were positive.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies collected and reported information about multisensory exercise, which included participants all females [31,32] . Of these participants, 30 were ataxic patients [33] , 73 were older adults with a history of falls [20,34,35] , 33 were older adults without fall history [35,36] , 18 were older adults with visual impairment [37] , 16 were diabetics with peripheral neuropathy [38] , and 21 were patients with essential tremor [39] . A total of 667 participants were included in the 20 studies, four studies were conducted in the United States, four in Canada, two in Brazil, and two in France, other studies in England, Indian, Sweden, and so on.…”
Section: Participants and Settingsmentioning
confidence: 99%
“…The total time spent in exercising during the multisensory exercise interventions varied from 0.5 [30,40] to 180 h [33] , while the intervention duration ranged from 2 [41] to 16 weeks [31] . Studies of intervention time showed that multisensory exercises worked within 6 weeks [34,38,42] , 8 weeks [20,39,43] , 12 weeks [36,37,44] ) respectively. However, there are still studies which reported effective intervention duration was less than 6 weeks or more than 12 weeks.…”
Section: Intervention Programsmentioning
confidence: 99%
“…These individuals walk 20-30% slower on par with the age matched healthy individuals. [13] The gait alterations include reduced cadence, decreased gait velocity, shorter stride length, increased stance time. Uneven surfaces are more challenging for these patients.…”
Section: Introductionmentioning
confidence: 99%